Malignant Futility in the Intensive Care Unit - Alev Öztaş; Burcu İleri Fikri; Zinet Aslancı; Güldem Turan (Türk Yoğun Bakim Derneği Dergisi)
Objective: The number of oncological patients whose life expectancy has been prolonged thanks to the developments in diagnosis and treatment modalities in the intensive care unit (ICU) is increasing. One of the most common reasons for ethics committee consultation is that patients and their families demand unnecessary restraint from doctors. Although clinical criteria are used to decide whether the applied treatment is useless, it is not sufficient alone to overcome the problems in this regard. The first aim of this study is to draw attention to the futil therapy applied in patients with terminal malignancies in our country and to help determine the necessary strategies to reduce the futility rate. The second purpose is to determine the cost of the futil therapy applied in the intensive care to the health system. Materials and Methods: The data of 127 patients with malignancy who were followed up in the ICU between 01 December 2020 and 31 December 2021 were analyzed retrospectively. Stage-4 patients aged 18 years or older with a diagnosis of malignancy, who were recommended palliative treatment by oncologists, and with inoperable, terminal stage, metastatic malignancy were considered as patients who received futile treatment and were included in this study. Results: Futil treatment was observed in 98 of 127 oncological patients treated in the ICU, and the mortality rate was 86.73% (n=85) in these patients.The cost of futile treatment to the health system was 1.071 intensive care days and $187,907.4 for these patients, who had a high mortality rate, during their stay in the ICU. Conclusion: With the relevant legal regulations to be made, the evaluation of terminal stage oncological patients by the ethics consultants and the determination of care protocols, and the opening of intermediary ICUs, it can be ensured that patients will have more qualified lifetime.